HYPERBARIC OXYGEN THERAPY: A KEY ROLE IN THE TREATMENT OF CEREBRAL GAS EMBOLISM - Ana Margarida Fernandes; Tatiana Fonseca; Ana Isabel Paixão; Paula Castelões (Sociedade Galega de Medicina Interna, 2020)
Stroke is an important cause of morbidity and mortality. The etiologies are varied. Gas embolism is a known complication of invasive procedures, which may complicate with cerebral embolization and ischemia. Benefits of hyperbaric oxygen therapy are recognized in cerebral gas embolism when started in the first hours after the event, which are fundamental for the vital prognosis.